The protective effect of a buckwheat-enriched diet on renal injury in high salt-induced hypertension in rats. Issue 8 (26th July 2016) - Cheng, Dai; Zhang, Xinyu; Meng, Meng; Han, Lirong; Li, Zheng; Hou, Lihua; Qi, Wentao; Wang, Chunling
Abstract : An excess of dietary salt is the most common factor that contributes to the pathogenesis of hypertension. Abstract : An excess of dietary salt is the most common factor that contributes to the pathogenesis of hypertension. Dietary management is deemed critical to prevent and treat hypertension. We aimed at evaluating the preventive effect of the buckwheat (BW)-enriched diet on high salt-induced elevation of blood pressure (BP) and renal injury in order to provide a new focus on the design of strategies to prevent hypertension. Control, high salt (HS)-treated (8%), HS + tartary buckwheat (TB) (8% HS + 15% TB), and a group of HS + common buckwheat (CB) (8% HS + 15% CB) rats were used for 7 weeks. BP was monitored periodically during the study by the tail cuff method. HS intake caused a significant increase of BP, the level of serum Na + compared to the control group. BW significantly prevented the increase of BP, attenuated oxidative damage, and improved Na + /K + -ATPase activity in HS treated rats. These results show that a diet supplemented with whole BW has beneficial effects on hypertension, by decreasing blood pressure values and oxidative stress.